106k views
5 votes
What scientific value for n will make this equation true?
(4.8 x 10^-3)(n) = 9.6 x 10^9

2 Answers

2 votes

Answer: 2.0 x 10^12

Explanation:

just answered on edge 2021

User Revoua
by
5.4k points
3 votes

Answer:

n = 2*
10^(12)

Explanation:

(4.8 *
10^(-3) )n = 9.6 *
10^(9)

Divide both sides by (4.8 *
10^(-3) )

(4.8 *
10^(-3) ) / (4.8 *
10^(-3) ) n = 9.6 *
10^(9) / 4.8 *
10^(-3)

n = 9.6 *
10^(9) / 4.8 *
10^(-3)

n = 9.6/4.8 *
10^(9) /
10^(-3)

n = 2 *
10^(9 - (-3))

n = 2*
10^(12)

User Taku
by
5.7k points